Identification of Bogor City Square Tourist Attraction Facilities As An Indikator Of Visitor Satisfaction - Maya Ayu Ardira; Rizki Nurul Nugraha; Parera Yumnarizq Susilo (West Science Social and Humanities Studies, 2024)
The title of this research is the identification of facilities in Bogor City Square as an indicator of visitor satisfaction. Research on the identification of facilities in Bogor City Square as an indicator of visitor satisfaction has a significant impact on the management and development of these tourist destinations. In the era of fierce competition in the tourism industry, a deep understanding of the factors that influence visitor satisfaction is the main key to the success of a tourist attraction. This research directly contributes to efforts to improve service quality in Bogor City Square, which in turn can increase the competitiveness and attractiveness of the destination. The place of this research is in Bogor City Square. The research method uses qualitative research. The data used are primary and secondary. The results showed that the diversity of facilities, involving a variety of attractions, activities, and services, provides a richer tourist experience and suits the needs of various visitor segments. Such diversity proved to be a key factor in creating an inclusive atmosphere and flexibility for visitors to customize their visit. The diverse facilities in Bogor City Square make a positive impression and motivate visitors to plan repeat visits and give positive recommendations to others.